Linear Canonical Transforms on the Zemanian Spaces (Global Journal of Science Frontier Research, 2012)
The objective of this paper is to make the theory of Linear canonical transform mathematically rigorous. Here we define the linear canonical transform on the Zemanian space , the space of functions of rapid descent, and prove some results. We have also discussed some operation formulae for linear canonical transform on this space.
Keywords: Fractional Fourier transform; Linear canonical transform; space